Synthesis of New N-Benzoyl-S-alkyl/aryl-dithiocarbamates - Aydin, Fatma; Aykac, Dogan; Dagci, Erdogan (Asian Journal of Chemistry, 2010)
New N-benzoyl-S-alky/aryldithiocarbamates were synthesized in moderate to good yields by the reactions of benzoyl isothiocyanate with substituted aryl- and akylthiols.